Protargol in veterinary surgery - Pyle, Charles A. (My University, 1907)
Introduction: Protargol is a fine yellowish brown powder, a compound of albumen and silver, odorless and with a weak metallic taste. The drug contains 8.3% silver and seems to be a salt containing silver in a masked form as well as a firm combination with a proteid. This product is soluble in one part of water, in glycerine and blood serum. It is not precipitated by alkaline sulphates, albumen, sodium chloride or acids and has a neutral reaction. It is superior to Silver Nitrate in being much less irritating, indifferent to sodium chloride and albumen and in that it does not discolor the skin and exceeds the Nitrate in certainty and efficiency of action. Protargol is a powerfully penetrating antiseptic and mild astringent in catarrhal and purulent inflammations of mucous cavities and tracts. In purulent wounds, abscesses, fistulous tracts it is effective in destroying bacteria and promoting healing. Protargol was first introduced into medicine in 1897 by Prof. Neisser, as a local medication for gonorrhoea in man. It is also used as a local treatment for catarrhal or purulent urethritis in the Human. The drug is indicated in acute catarrhal and purulent conjunctivitis in from one half to ten per cent aquous solutions. In tubercular ulcers, fistulous tracts it is reported very effectual. In catarrhal and ulcerative affections of the ear it is indicated. Abscesses, purulent arthritis, persistant granulating wounds and wounds of the foot yield readily to this drug. Internally the drug is indicated in canine practice as a relief of hemorrhages and ulcerations of the alimentary tract and purulent inflammations of the genito urinary tract. The drug in powder or in solution must be preserved from the action of light or heat. In making, the solutions the menstruum should be cold and the drug placed on the surface and allowed to dissolve slowly or with gentle agitation. The solution is reddish brown in color depending on the strength of the drug.
Citation: Pyle, Charles A. Protargol in veterinary surgery. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Protargol; Medicine; Pharmaceuticals; Veterinary Surgery; Theses